Size-dependent regulations, firm size distribution, and reallocation - François Gourio; Nicolas Roys (Quantitative Economics, 2014)
In France, firms that have 50 employees or more face substantially more regulation than firms that have less than 50. As a result, the size distribution of firms is visibly distorted: there are many firms with exactly 49 employees. We model the regulation as the combination of a sunk cost that must be paid the first time the firm reaches 50 employees and a payroll tax that is paid each period thereafter when the firm operates with more than 50 employees. We estimate the model using indirect inference by fitting the discontinuity of the size distribution. The key finding is that the regulation is equivalent to a combination of a sunk cost approximately equal to about 1 year of an average employee salary and a small payroll tax of 0.04%. Our structural model fits well the discontinuity in the size distribution. Removing the regulation improves labor allocation across firms, leading in steady state to an increase in output per worker slightly less than 0.3%, holding the number of firms fixed. However, if firm entry is elastic, the steady-state gains are an order of magnitude smaller.
Keywords: 330; Firm size distribution; regulation; threshold effect; reallocation